PROTOTYPE SISTEM OTOMASI LAMPU TAMAN BERBASIS ARDUINO UNO: GARDEN LIGHT AUTOMATION SYSTEM PROTOTYPE BASED ON ARDUINO UNO - Darmawan, Erwin (Jurnal Teknologi Komputer dan Informatika, 2024)
So far, controlling garden lights has used human power to turn the lights on and off. To replace the use of humans in controlling garden lights, a Garden Light Automation system was created. The aim of making this tool is to control garden lights automatically. In making this tool, hardware is used in the form of RTC, Arduino Uno and Relay. The RTC functions to activate the time, the Arduino Uno functions to process data and information from the automation system created and the relay functions to disconnect and connect the electricity flow from PLN to the garden lights. The tool testing results are in accordance with the tool manufacturing planning.